Relationship Between Preoperative Shoulder Osteoarthritis Severity Score and Postoperative PROMIS-UE Score After Rotator Cuff Repair. Issue 1 (4th January 2023) - Davies, Michael R.; Kucirek, Natalie; Motamedi, Daria; Ma, C. Benjamin; Feeley, Brian T.; Lansdown, Drew
Background: Mild to moderate glenohumeral joint osteoarthritis is a common finding among patients who are evaluated for rotator cuff tears. However, the impact of preoperative shoulder joint degeneration on patient-reported outcomes after rotator cuff repair (RCR) is not well-established. Purpose: To apply the magnetic resonance imaging (MRI)–based Shoulder Osteoarthritis Severity (SOAS) score to the evaluation of patients undergoing RCR and determine the relationship between preoperative shoulder pathology present on MRI and postoperative Patient-Reported Outcomes Measurement Information System–Upper Extremity (PROMIS-UE) scores. Study Design: Case-control study; Level of evidence, 3. Methods: Seventy-one MRI scans corresponding to 71 patients were analyzed by 2 independent reviewers and scored using the SOAS criteria. Intraclass correlation coefficients were calculated for total SOAS score as well as for each subscore. Spearman correlations were calculated between averaged SOAS scores, patient characteristics, and PROMIS-UE scores. Linear regression analysis was performed between the independent variables of patient age, sex, body mass index, and significant SOAS score components determined by univariate analysis with the dependent variable of PROMIS-UE score. Significance was defined as P < .05 for univariate analyses and < .0125 for multivariate analyses using the Bonferroni correction. Results: The mean PROMIS-UE score of this cohort was 51.5 ± 7.4, while the mean total SOAS score was 21.5 ± 8.4. There was a negative correlation between total SOAS score and postoperative PROMIS-UE score ( r = –0.24; P = .040). Both cartilage wear ( r = –0.33; P = .0045) and acromioclavicular joint degeneration ( r = –0.24; P = .048) individually demonstrated negative correlations with PROMIS-UE score. When a multivariate linear regression with Bonferroni correction was applied to the significant variables identified in univariate analysis along with patient characteristics, none were independently correlated with PROMIS-UE score. Conclusion: In this cohort of patients undergoing RCR, increasing preoperative total SOAS score was predictive of lower postoperative PROMIS-UE scores. SOAS subscores with the strongest negative correlations with PROMIS-UE scores included cartilage wear and acromioclavicular joint degeneration. The cartilage subscore was negatively correlated with PROMIS-UE scores independent of patient factors in multivariate analysis.